Food waste recovery : processing technologies and industrial techniques - Galanakis, Charis Michael (Academic Press is an imprint of Elsevier, 2015)
Food Waste Recovery: Processing Technologies and Industrial Techniques acts as a guide to recover valuable components of food by-products and recycle them inside the food chain, in an economic and sustainable way. The book investigates all the relevant recovery issues and compares different techniques to help you advance your research and develop new applications. Strong coverage of the different technologies is included, while keeping a balance between the characteristics of current conventional and emerging technologies. This is an essential reference for research outcomes. Presents a holi.